PENGARUH PENDIDIKAN KESEHATAN DENGAN MENGGUNAKAN METODE CERAMAH TERHADAP SIKAP IBU TENTANG PAP SMEAR PADA IBU – IBU DI BPS Ny. TIAS KHOLILI, A.Md., Keb MLOKOREJO – PUGER KABUPATEN JEMBER - Riza Umami (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2013)
Cervical cancer is a malignancy that occurs on the cervix (cervical) which is the lowest part of the uterus that protrudes into the top of hole intercourse (vaginal). The cause is not known for certain, but 95% of cases were HPV (Human Pappiloma Virus) positive. In 2007 the Chairman of the Central Executive III Indonesian Cancer Foundation (ICF), Sumaryati Aryoso said that each year there are 15,000 women who develop cervical cancer in Indonesia. Of this amount, 8,000 of whom died. The purpose of this study to determine the effect of health education lectures using maternal attitudes about the Pap smear.The study design used was the type of research Pre-Experiment. The population in this study were mother-tongue in the BPS Ny. Tias Kholili, A.Md., Keb Mlokorejo - Puger Jember district with a sample of 20 people and the sampling technique used is total sampling. From the research that has been conducted on February 7, 2012 showed that positive attitudes about the Pap smear before Mother's health education were 14 respondents (70%) while negative attitudes about the Pap smear before Mother's health education is 6 respondents (30%). Similarly, a positive attitude about the Pap smear after the mother of health education as much as 19 respondents (95%) while negative attitudes about the Pap smear after Mother's health education is still common although only one respondent (5%). Based on Chi-square statistical test with a significance level of 5% 6.705 obtained results, thus this study received H1 which means no influence of health education lectures using Mom's attitude about Pap smears.